Modelagem de requisitos de software de tempo-real usando SysML e MARTE - Ribeiro, Fabíola Gonçalves Coelho (2013)
The specication, analysis and design of real-time systems (RTS) are activities that are highly dependent on an eective understanding of the application domain and on the completeness of the representation of their primordial requirements. The use of modelbased approaches for the development of RTS systems tend to contribute to minimizing the complexity of the system development process. The UML has been strongly used in recent years for modeling real-time software. However, UML alone does not represent with completeness important characteristics of these systems, such as timing requirements. UML is a language that has several extensions capabilities enabling the creation of specic proles. This work will explore the use of UML proles SysML and MARTE to modeling software requirements of RTS for the control of road trac. The main objective is to demonstrate the application of SysML with MARTE stereotypes, which enables the modeling, representation, classication, documentation and, also, for dened criteria of traceability of real-time software requirements. The proposed approach was shown to be relevant in the context of the specication, analysis, classication and modeling requirements for real-time systems. The SysML Requirements diagram shows explicitly the various types of relationships between dierent requirements, increasing the spectrum of understanding and dening the requirements of a real-time system. The MARTE prole complemented the precision of scenario with functional non annotations well formed, in general timing requirements. The concepts of SysML and MARTE, articulated in the SysML Requirements diagram are highly complementary covering many of the purposes of specifying requirements for real-time systems.